Studi Ableism pada Mahasiswa Muslim - Pramesti Noer Aliffah; Hamdan, Stephani Raihana (Bandung Conference Series: Psychology Science, 2024)
Abstract. Indonesia has implemented inclusive education that respects diversity and is non-discriminatory. On the other hand, people with disabilities in Indonesia still face obstacles in their social life such as discrimination against people with disabilities (ableism), especially in higher education. In Islam, Allah has created humans in the most perfect form. Islam emphasizes the value of deeds and good deeds rather than physical perfection, so Islam views people with disabilities and other humans equally, and also condemns all forms of discriminatory actions against people with disabilities. Everyone has the potential to be ableist to varying degrees, which can be high and low. In addition, ableism can be overt or covert (unconscious). Ableism in education will only create invisible barriers between people with disabilities and non-disabled people so that a climate of inclusivity is not created. This study aims to determine the level of ableism in Muslim students. This study used an online survey method involving 298 students of Bandung Islamic University. The measuring instrument used was the Symbolic Ableism Scale (Friedman & Awsumb, 2019) which was adapted into Indonesian by the researcher. The results of this study indicate that the level of ableism in non-disabled UNISBA students is low. The low level of ableism is owned by students who are female and have had direct interaction with people with disabilities, especially with physical disabilities. Abstrak. Indonesia telah menerapkan pendidikan inklusif yang menghargai keanekaragaman dan tidak diskriminatif. Disisi lain, penyandang disabilitas di Indonesia masih menghadapi hambatan dalam kehidupan sosialnya seperti diskriminasi terhadap penyandang disabilitas (ableism), khususnya dalam mengenyam pendidikan tinggi. Dalam Islam, Allah telah menciptakan manusia dengan bentuk yang paling sempurna. Islam menekankan nilai amal perbuatan dan perbuatan baik daripada kesempurnaan fisik, sehingga Islam memandang sama antara penyandang disabilitas dan manusia lainnya, juga mengecam segala bentuk tindakan diskriminatif terhadap penyandag disabilitas. Setiap orang memiliki potensi sebagai ableist dengan tingkatan yang bervariatif, dapat tinggi dan dapat pula rendah. Selain itu, ableist dapat bersifat secara terbuka atau secara tersembunyi (tidak disadari). Ableism di dalam pendidikan hanya akan membuat invisible barriers antara penyandang disabilitas dengan non-disabilitas sehingga iklim inklusivitas tidak tercipta. Penelitian ini bertujuan untuk mengetahui tingkat ableism pada mahasiswa muslim. Penelitian ini menggunakan metode survei daring yang melibatkan 298 mahasiswa Universitas Islam Bandung. Alat ukur yang digunakan adalah Symbolic Ableism Scale (Friedman & Awsumb, 2019) yang diadaptasi ke dalam Bahasa Indonesia oleh peneliti. Hasil penelitian ini menunjukkan bahwa tingkat ableism pada mahasiswa non-disabilitas UNISBA tergolong rendah. Tingkat ableism yang rendah dimiliki oleh mahasiswa berjenis kelamin perempuan dan pernah berinteraksi langsung dengan penyandang disabilitas, terutama dengan jenis disabilitas fisik.